10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
BACKGROUND: Breastfeeding challenges are common in postnatal settings, particularly in low-resource communities. Timely and skilled support by frontline workers such as Auxiliary Nurse Midwives (ANMs) and Community Health Officers (CHOs) is essential. RESEARCH AIM: This study was conducted to develop and validate a structured Objective Structured Clinical Examination (OSCE) based tool-LactManage-to assess the skills of frontline workers in managing breastfeeding problems at the community level. METHOD: A prospective, three-phase study was conducted from January to June, 2024. In Phase 1, a rigorous literature review including, national programs and the World Health Organization's 10 steps to successful breastfeeding, was performed to develop 10 OSCE stations covering key breastfeeding challenges. In Phase 2, content validity was assessed by 20 experts, and face validity by 30 lay experts. In Phase 3, construct validity was assessed using the final tool administered to 85 frontline health workers in the community setting. Content and face validity indices at item and scale level, along with kappa, were calculated. Construct validity was assessed using the Intraclass Correlation Coefficient and a known-groups t-test. RESULTS: The tool demonstrated high content (S-CVI/Avg = 0.92) and face validity (S-FVI/Avg = 0.99). The values of the Intraclass Correlation Coefficient had a range from 0.75 to 0.99 which is suggestive of good to excellent reliability. CHOs had significantly higher scores than ANMs in the known-groups t-test (p < 0.001) which supports construct validity. CONCLUSION: Our study concluded that the LactManage tool is valid and reliable for assessing the skills of the frontline workers on management of breastfeeding problems.